Réponses

2013-02-10T15:07:05+01:00

Salut,

 

11)

A = (x+1)² - 2(x+1)

A = (x+1)(x+1-2)

A = (x+1)(x-1)

A = x² - 1

 

B = (2x + 3)² + (x - 2)(2x+3)

B = (2x+3)(2x+3+x-2)

B = (2x+3)(3x+1)

 

C = (3x-5)² - (x+4)(3x-5)

C = (3x-5)(3x-5-x-4)

C = (3x-5)(2x-9)

 

12)

E = (2t + 1)² - (t+1)²

E = (2t + 1 + t + 1)(2t  +1 -t - 1)

E = (3t + 2)t

 

F = (3t - 7)² - 25

F = (3t - 7 + 5)(3t - 7 - 5)

F = (3t - 2)(3t - 12)

 

G = (3t + 4)² - (2t + 3)²

G = (3t + 4 + 2t + 3)(3t  +4 - 2t - 3)

G = (5t + 7)(t + 1)

 

Voilà, cordialement.

Si tu penses que c'est la meilleure réponse, nhésite pas à cliquer sur le bouton ;)

Si tu as besoin d'aide, envoie moi un message.

A bientôt ;)

Alexis.